ADULT AND YOUTH LITERACY PROGRAMS IN THE FACE OF SHUT DOWNS DURING THE COVID-19 PANDEMIC - Enna Carvajal; Judith Kalman (Universidad Nacional del Nordeste, 2022)
This article argues that although the closure of schools during the Covid 19 emergency and the transfer of education to the home generated an unstable and challenging situation for the directors, teachers and students of the regular educational systems, for the literacy courses and the education of young people and adults (EPJA) the challenge was even greater due to the already precarious working conditions of these educational systems. Given the urgency, in some countries program providers sought to give continuity to the educational programs. Efforts to achieve this evolved during the pandemic included different uses of digital technologies. The authors conclude that while we have seen in the Latinamerican region an important migration to digital environments, the use of videos and educational television, this has not resulted in substantive innovations in conceptualizations and educational activities for adult literacy programs.